Mission concept development of an equatorial constellation of CubeSats for space-based internet of things for the Singapore region - Tan, Clement Hong Ye (2019)
This project is an extension of research into SaRC’s next satellite mission RIMAU. RIMAU will be a satellite constellation mission in order to be an efficient technology enabler for disaster recovery or for communicating with sensors in the event of the terrestrial network being unavailable. The constellation will also provide continuous common volume measurements and provide an unprecedented opportunity to map the ionosphere regionally This project has investigated the feasibility of such a constellation through the use of STK simulation software. The primary goal of this project was to observe the equatorial orbit coverage and data rate of a 6-satellite constellation. The scenarios that were investigated in this report included 1. Revisit time of a single satellite 2. The amount of uplink time of a 6-satellite constellation and determine if it provides constant communication with the earth station 3. The amount of equatorial coverage and uplink time of a 6-satellite constellation released at the same time with varying amplitudes. Finally, a conclusion of the effects of the various orbital parameters on the feasibility of a 6-satellite constellation is available at the end of the report.